Raised plasma homocysteine as a risk factor for retinal vascular occlusive disease. Issue 2 (1st February 2000) - Cahill, Mark; Karabatzaki, Maria; Meleady, Ray; Refsum, Helga; Ueland, Per; Shields, Denis; Mooney, David; Graham, Ian
Abstract : BACKGROUND/AIMS: A moderately elevated plasma concentration of the sulphur amino acid homocysteine is an independent risk factor for atherosclerotic vascular disease. Many of the risk factors associated with coronary, cerebral, and peripheral atherosclerotic vascular disease are common to retinal vascular occlusive disease but it is unclear whether elevated plasma concentrations of homocysteine are also associated with such disease. This study assessed the relation between retinal vascular occlusive disease and elevated levels of plasma total homocysteine (tHcy). METHODS: A retrospective case-control study involving hospital based controls and cases with retinal artery, central retinal vein (including hemiretinal vein), and branch retinal vein occlusions was performed. The relation between elevated tHcy, defined as a level greater than or equal to 12 μmol/l and risk of retinal vascular occlusive disease was examined. RESULTS: 87 cases of retinal vascular occlusive disease including 26 cases of retinal artery occlusion, 40 cases with central retinal vein occlusion, and 21 cases of branch retinal vein occlusion were compared with 87 age matched controls. Mean tHcy levels were higher in all disease groups and this difference was significant in patients with retinal artery occlusions (p= 0.032) and patients with central retinal vein occlusion (p=0.0001). When adjusted for known cardiovascular risk factors, tHcy was an independent risk factor for retinal vascular occlusive disease (OR 2.85 (95% CI 1.43–5.68)). CONCLUSIONS: Elevated tHcy is an independent risk factor for retinal vascular occlusive disease. Assessment of tHcy may be important in the investigation and management of patients with retinal vascular occlusive disease.